Effects of Demo Kit on Remediating Senior School Students’ Misconceptions in Mitosis and Meiosis in Ilorin, Nigeria - Akindeyi Luwoye (Commonwealth of Learning, 2021)
This study investigated the influence of the demo kit on remediating misconceptions held by senior school students in mitosis and meiosis. The quasi-experimental design of the pre-test, post-test, non-equivalent control group was adopted for the study. A multistage sampling technique was used to select 60 male and female biology students from two senior secondary schools in Ilorin metropolis. The instruments used for data collection was the Mitosis and Meiosis Conception Package (MMCP). Frequencies and chi-square were used to answer the research questions and test the null hypothesis, respectively. The findings revealed that biology students held misconceptions on mitosis and meiosis before and after instructions. However, there was a significant difference in the number of misconceptions held by students taught using the demo kit and those taught with the conventional method. It was recommended that biology teachers adopt the use of the demo kit for remediating students’ pre-and post-instructional misconceptions on mitosis and meiosis.